Anesthetic sensitivity of the Gloeobacter violaceus proton-gated ion channel - Weng, Yun (2009)
INTRODUCTION: Receptors from the superfamily of pentameric ligand-gated ion channels including gamma aminobutyric acid type A (GABA(A)), glycine, 5HT(3), and neuronal nicotinic acetylcholine receptors are modulated by anesthetics in concentrations that are used clinically. Recently, a prokaryotic member of this family (denoted GLIC) was cloned from the cyanobacterium Gloeobacter violaceus, its electrophysiology was characterized, and its three dimensional x-ray diffraction crystal structure was determined. Here we report its modulation by nine common anesthetics. Our goal was to identify agents that modulated GLIC and which therefore might merit further investigation by structural methods. METHODS: We studied the modulatory effect on GLIC of halothane, isoflurane, sevoflurane, desflurane, xenon, nitrous oxide, etomidate, propofol, and ethanol. GLIC was expressed in Xenopus laevis oocytes and studied using two-electrode voltage clamping. RESULTS: GLIC was potently inhibited by halothane, sevoflurane, isoflurane, desflurane, and propofol, with concentrations producing 50% inhibition (IC(50)s) of 0.07 mM, 0.15 mM, 0.06 mM, 0.03 mM, and 0.5 μM, respectively. Hill coefficients for these anesthetics were significantly less than 1: 0.27, 0.27, 0.32, 0.25, and 0.42, respectively. Hill coefficients for xenon and etomidate were not different from 1. IC(50)s for xenon and etomidate were 105 % atmospheres and 73 μM respectively. 200 mM ethanol did not modulate channel currents, nor did 100% nitrous oxide. A two-site model fit the data for desflurane and halothane better than a one site model. CONCLUSION: GLIC is modulated by many anesthetics at clinically relevant concentrations. We observed three patterns of modulation. Halogenated volatile anesthetics (desflurane, halothane, isoflurane, sevoflurane) and propofol potently inhibited currents through GLIC, with Hill numbers averaging approximately 0.3 indicating negative cooperativity. A two site model fit the data for desflurane and halothane better than a one site model. Less potent drugs (xenon, etomidate) modulated GLIC at higher concentrations and over a narrower concentration range, with Hill numbers not different than 1. The modulation by xenon occurred at clinically relevant concentrations. The modulation by etomidate occurred above clinical concentrations. Ethanol and nitrous oxide did not modulate currents through GLIC at surgical anesthetic concentrations. These studies, together with the atomic scale structure of GLIC, lay the groundwork for further mechanistic studies of these allosteric effects.